Growth and Human Development: Comparative Latin American Experience. - Ranis, G; Stewart, F (Economic Growth Center (Yale University), 2001)
This paper seeks to examine the interdependence between economic growth (EG) and human development (HD). It is concerned with changes in per capita income and its two-way relationship with the basic societal objective of human development. Regressions across various Latin American countries are run for 1960-92. Country performance is separated into virtuous/vicious cycles or HD/EG lopsidedness. The study makes an attempt to correct the commonly held view that ensuring increases in economic growth automatically leads to advances in human development. Human development has to occur prior to or simultaneous with improvements in economic growth, if a country is to reach a virtuous cycle. The Latin American experience indicates that a balanced approach to development has to be adopted. It is imperative to focus on human development from the outset of any reform program, as policies that emphasize economic growth alone are futile in sustaining high levels of human development.